Analisis Semantik Surga: Jannah, Hada’iq, Raudhah Menurut Prinsip Makna Goeffrey Leech - Nurjannah; Bashori (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2025)
This article examines the semantic meanings of three Qur’anic terms related to the concept of paradise -Jannah, Hadāʾiq, and Raudhah- by using Geoffrey Leech’s semantic framework. The study aims to identify the root words, basic meanings, and contextual usage of these terms in Qur’anic verses, while applying Leech’s semantic principles to clarify their semantic distinctions. Employing a descriptive qualitative method with a structural semantic approach, this research analyzes how each term contributes to the Qur’anic construction of paradise. The findings indicate that Jannah is the most frequently used term and primarily denotes an eschatological and eternal paradise. In contrast, Hadāʾiq is predominantly employed in a worldly context to describe lush and well-cultivated gardens, while Raudhah carries a more symbolic and spiritual nuance, particularly as it is further elaborated in the Hadith tradition. These variations suggest that the Qur’an presents the concept of paradise through a layered and contextual semantic network rather than a single, uniform meaning. This study highlights the importance of semantic and linguistic approaches in preventing reductive interpretations of Qur’anic terminology and in fostering more critical and reflective engagement with the Qur’anic text. Keywords: Qur’anic Semantics, Paradise in the Qur’an, Geoffrey Leech’s Semantic Theory